Geoformas y suelos en el Valle del Río Traful, Provincia del Neuquén - Ferrer, J.A. (1999)
Landforms and soils in the Traful River Valley, Neuquén Province. The Andes Patagónicos Region is characterised by the presence of strong west-east bioclimatic, geomorphological and lithostratigraphical gradients, that controlled the genesis and geographical distribution of soils. In this contribution soil-landscape relationships in a sector of a transitional zone in the northern Andes Patagónicos are studied. The Traful River valley is located in Neuquén Province aproximately at 40°40′S and 71°15′W. Diverse geomorphological units were distinguished which were formed through glacial and fluvioglacial action, and partially modified in recent times by fluvial and eolian processes and by mass wasting. Holocen ashes and lapilli were deposited in different volcanic events and constitute the soils'main parent material. We recognize soils belong to three orders: entisols, mollisols and andisols. A strong gradient of variations in soils properties was observed. The Andisolization process decrease with distance from the Cordillera zone. © 1999 Asociación Geológica Argentina.